ANALISIS INDEKS KEBAHAGIAAN KEPALA SEKOLAH DAN GURU DALAM KEGIATAN BIMBINGAN TEKNIS PROGRAM SEKOLAH PENGGERAK - Rasidi Rasidi; Robiul Fitri Mashitoh (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2022)
“Sekolah Penggerak” is a policy of the Ministry of Education, Culture, Research, and Technology, since 2021. The program is an effort to realize Indonesia's education vision in realizing